SURVEY OF THE TECHNIQUES OF RAPID SEQUENCE INTUBATION BY PRACTICING ANESTHESIOLOGISTS IN TERTIARY CARE HOSPITALS OF KARACHI - A CROSS-SECTIONAL SURVEY - Dr. Muhammad Waqas Khan; Dr.Syed Hassan Adil Rizvi; Dr. Komal Zafar; Dr. Atif Parvez; Dr. Asir Nasiruddin; Sajid Atif Aleem (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Rapid Sequence Induction (RSI) is a key technique to reduce aspiration risk during emergency surgeries, involving preoxygenation, intravenous anesthesia, cricoid pressure, and rapid intubation without mask ventilation. Debate persists over optimal positioning and cricoid pressure application, with variations in practice. While some believe preoxygenation suffices for low-risk patients, others stress strict protocols for safety. Further research on these discrepancies could help standardize techniques and reduce this preventable complication. Objective To evaluate the techniques of Rapid Sequence Intubation (RSI) among anesthesiologists in tertiary care hospitals of Karachi and identify variations in practice. Materials and Method: This cross-sectional investigation, performed from November 2021 until May 2022 across nine tertiary medical centers in Karachi, aimed to assess anesthesia practices among 87 anesthesiologists. Employing a non-random, successive sampling method, the research targeted consultants, specialists, and final-year FCPS residents. Information was collected through self-administered questionnaires regarding demographics and anesthesia practices, such as patient positioning and cricoid pressure utilization. Analysis in SPSS 26.0 involved descriptive and inferential analytics to explore practice patterns and relationships, with statistical significance established at p<0.05. Results: Among respondents, 64% were male and 35.6% female, with most aged 31-40 years (42.5%) and 34.5% having 6-10 years of experience. Only 4.6% of anesthesiologists were trained in using gastric ultrasound, while 89.7% followed standard RSI procedures. In cases of intestinal obstruction, 62.1% of patients were positioned supine, compared to 77.0% in non-obstruction cases. Cricoid pressure was applied in 94.4% of obstruction cases, and nasogastric tubes were inserted in 56.3% of those patients. Conclusion: It may be inferred that the majority of practitioners adhered to standardised protocols, including regular cricoid pressure and supine placement, especially in non-obstructed patients. The use of nasogastric tubes and gastric ultrasonography was irregular and uncommon. The inconsistency in procedures underscores the necessity for standardisation and enhanced training in sophisticated techniques such as stomach ultrasonography and patient positioning, hence guaranteeing safer anaesthesia care.